Adverse Events in Connective Tissue Disease–Associated Pulmonary Arterial Hypertension. Issue 9 (September 2015) - Rhee, Rennie L.; Gabler, Nicole B.; Praestgaard, Amy; Merkel, Peter A.; Kawut, Steven M.
<x xml:space="preserve">Abstract</x> Objective Patients with connective tissue disease (CTD)–associated pulmonary arterial hypertension (PAH) have a poorer prognosis compared to those with idiopathic PAH, but little is known about the differences in treatment‐related adverse events (AEs) and serious adverse events (SAEs) between these groups. This study was undertaken to characterize these differences. Methods Individual patient‐level data from 10 randomized controlled trials of therapies for PAH were obtained from the US Food and Drug Administration. Patients diagnosed as having either CTD‐associated PAH or idiopathic PAH were included. A treatment‐by‐diagnosis interaction term was used to examine whether the effect of treatment on occurrence of AEs differed between patients with CTD‐associated PAH and those with idiopathic PAH. Studies were pooled using fixed‐effect models. Results The study sample included 2, 370 participants: 716 with CTD‐associated PAH and 1, 654 with idiopathic PAH. In the active treatment group compared to the placebo group, the risk of AEs was higher among patients with CTD‐associated PAH than among those with idiopathic PAH (odds ratio [OR] 1.57, 95% confidence interval [95% CI] 1.00–2.47 versus OR 0.94, 95% CI 0.69–1.26; P for interaction = 0.061), but there was no difference in the risk of SAEs in analyses adjusted for age, race, sex, hemodynamic findings, and laboratory values. Despite the higher occurrence of AEs in patients with CTD‐associated PAH assigned to active therapy compared to those receiving placebo, the risk of drug discontinuation due to an AE was similar to that in patients with idiopathic PAH assigned to active therapy (P for interaction = 0.27). Conclusion Patients with CTD‐associated PAH experienced more treatment‐related AEs compared to those with idiopathic PAH in therapeutic clinical trials. These findings suggest that the overall benefit of advanced therapies for PAH may be attenuated by the greater frequency of AEs.